Development and Alterations in Cerebellar Glutamate Levels and Structure in Preterm Infants - GONG, He; REN, Qingfa; YIN, Zhijie; LIU, Quanyuan; WANG, Jing; LIU, Yuwei; XU, Donghao; XU, Lumeng; QI, Kai; XIA, Shuyuan; JIANG, Zhongde; LI, Xianglin (IEICE Transactions on Information and Systems, 2025)
With the development of neuroscience and psychology, the cerebellar role in higher-order functions has been increasingly recognized. Premature birth has an impact on cerebellar development and increases the risk of neurodevelopmental disorders. This study aimed to evaluate the development and alterations of glutamate levels and volumes in cerebellar subregions in preterm infants and investigate the relationship of glutamate and volumes. 70 preterm infants and 22 full-term infants underwent glutamate chemical exchange saturation transfer (GluCEST) and sampling perfection with application optimized contrasts using different flip angle evolutions (SPACE). Custom-written scripts in MATLAB were used to process GluCEST images to obtain glutamate levels, and volumes were obtained by ITK-SNAP. Both glutamate levels and volumes in cerebellar subregions in preterm infants were positively correlated with postmenstrual age. Furthermore, when compared to full-term infants, the glutamate levels of preterm infants at term-equivalent age were higher. No correlation was found between glutamate and volume. The metabolite and structure of preterm infants in cerebellar subregions were altered even in the absence of significant brain structure damage. These findings may help probe the pattern of brain maturation and identify potential neurodevelopmental disorders in preterm infants.